Analysis of Factors Affecting the Fee Audit at Indonesian State-Owned Enterprises - Agus Widarsono; Lita Natalia (Jurnal ASET (Akuntansi Riset), 2024)
The objective of this study is to examine the variables that impact the fees charged for audits conducted at Indonesian State-Owned Enterprises. These variables include the size and complexity of the firm, the reputation of the auditor, and the length of the audit tenure. The used in this study is quantitative, employing a causal associative design. The study utilized a purposive sampling technique to choose 36 state-owned companies (SOEs) from various industrial clusters over a period of 4 years (2018-2021). This study utilizes descriptive statistical analysis and panel data regression analysis methodologies, after doing various classical assumption tests. After doing an analysis and debate, it can be stated that Company Complexity and Auditor Reputation have a substantial impact on Audit Fees at Indonesian State-Owned Enterprises. However, Company Size and Audit Tenure do not have a major effect on audit fees. Agency Theory and the findings of this study can assist corporations in accurately forecasting the audit fees that will be charged by KAP. This research can serve as a valuable resource for auditors when seeking audit assignments, ensuring that they are compensated appropriately. No prior research has specifically examined the audit fee policy for State-Owned Enterprises.